Efficient reduction of optimal disinfectant booster station placement formulations for security of large-scale water distribution networks. Issue 8 (3rd August 2017) - Seth, A.; Hackebeil, G. A.; Klise, K. A.; Haxton, T.; Murray, R.; Laird, C. D.
ABSTRACT: In response to a contamination incident in water distribution networks, disinfectant booster stations can be used to neutralize the contaminant and protect the public. In this paper, two mixed-integer linear programming formulations are proposed for optimal placement of disinfectant booster stations. The first formulation minimizes the contaminant mass consumed by the public, while the second formulation minimizes the number of people who ingest the contaminant above a mass threshold. The proposed formulations consider uncertainty in both the location and time of the contamination incident, resulting in an intractably large stochastic programming problem. This manuscript proposes a series of reductions that decrease the size of the problem by up to five orders of magnitude. The results show that the use of a small number of disinfectant booster stations can be very effective as a response strategy.